2021
DOI: 10.1186/s12931-020-01610-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled high molecular weight hyaluronan ameliorates respiratory failure in acute COPD exacerbation: a pilot study

Abstract: Background Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) carry significant morbidity and mortality. AECOPD treatment remains limited. High molecular weight hyaluronan (HMW-HA) is a glycosaminoglycan sugar, which is a physiological constituent of the lung extracellular matrix and has notable anti-inflammatory and hydrating properties. Research question We hypothesized that inhaled HMW-HA will improve outcomes in AECOPD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…One strategy is to counteract changes in the extracellular matrix by giving glycosaminoglycans such as hyaluronic acid or heparan sulfate. A placebo-controlled randomised trial 250 showed that high-molecular-weight hyaluronan ameliorated respiratory failure in patients with severe COPD exacerbations. Several antivirals are also in the pipeline, including a dry-powder formulation of ribavirin.…”
Section: Exacerbationsmentioning
confidence: 99%
“…One strategy is to counteract changes in the extracellular matrix by giving glycosaminoglycans such as hyaluronic acid or heparan sulfate. A placebo-controlled randomised trial 250 showed that high-molecular-weight hyaluronan ameliorated respiratory failure in patients with severe COPD exacerbations. Several antivirals are also in the pipeline, including a dry-powder formulation of ribavirin.…”
Section: Exacerbationsmentioning
confidence: 99%
“…The efficacy of NIPPV in the treatment of severe respiratory failure has been clinically recognized [ 12 , 13 ]. Its mechanism of action is mainly to re-expand atrophied alveoli through effective ventilation, to improve respiratory muscle function, and reduce oxygen consumption, thereby correcting hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support a novel proposed model of S-protein-induced cell injury ( Figure 7 ): beyond the well-described interaction of the S-protein with host alveolar epithelia via the receptor human angiotensin-converting enzyme 2 (hACE2) (25; 47; 51), the S-protein also exerts pathological effects (changes in Proteome, E2F1, CREB, p65 activation) independent of ACE2. Furthermore, HMW-HA, which is naturally found in mammalian airways (1; 17), and can also be given pharmacologically (18), attenuates the deleterious effects of S-protein ( Figure 7 ). Thus, our findings suggest a novel injury pathway and a novel treatment agent for COVID-19 associated lung injury.…”
Section: Discussionmentioning
confidence: 99%